The Motivation of Muzakki to Pay Zakah: Study at The Baitul Mal Aceh - M Shabri Abd Majid (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
This study empirically explores the factors motivating Muzakki (zakat payers) to pay zakat at the Baitul Mal Aceh, Indonesia. The factors motivating Muzakki to pay zakat investigated in the study comprises culture, regulation, motivation, and Muzakki understanding on zakat. 600 questionnaires were disseminated to the respondents, which were selected based on the convenience sampling technique. Then, the data were analysed using a binary logistic regression. The results of this study showed that culture, regulation, motivation, and understanding of the Muzakki on zakat significantly and positively affected the decision of Muzakki to pay their zakat at the Baitul Mal Aceh. This study implies that in order Muzakki to pay their zakat at the Baitul Mal, Islamic cultures should be preserved among Achenese, government should enhance regulation pertaining zakat management and the people of Aceh need to be equipped with the relevant knowledge on the obligation of zakat payment. DOI: 10.15408/sjie.v6i1.4302